Trust: An esential key for waqf crowdfunding - Suhaili, Nur Aqidah; Palil, Mohd Rizal; Ismail, Nur Azlin; Husin, Rohayati (2017)
Purpose - Off all the recent growing philanthropy innovative advances, websites crowdfunding being one of the most impressive ones.This success is due to an exciting, emerging, and attesting crowdfunding intermediary’s that viable to attract waqf and charity donations. crowdfunding is a manner of fundraising that is done by asking a large crowd of people to contribute money to support a specific cause for instance an artistic project, a philanthropic project or a business venture.These contributions can vary in amount from a few dollars to hundreds of thousands, the funding is achieved by pooling all of these collections, big or small, together to achieve the larger goal for the fundraisers to be able to achieve or complete the aimed project.In general, research on crowdfunding investigated few areas such as identifying differences types of crowdfunding’s, legal ramifications of crowdfunding, security laws, usage of crowdfunding as a price discrimination model, and view of crowdfunding as pre-ordering transaction from consumerism perspective.This paper intends to visualize on the potential of digital based crowdfunding as collaborative waqf funding platform. The study aims to uncover how can the relationship between Islamic crowdfunding participants is influenced by the trustworthiness and credibility of the organizers and platforms could contribute to a reliable environment of the virtual setting of transactions.The scope of this study is limited to Islamic based crowdfunding that carry waqf values and included organizers whose names are well-known.Methodology - The case study is selected as the main research strategy for investigating the research questions.The main reason for selecting case studies because it provides some good insights into complex issues on a limited number of events or conditions and their relationship.There are critics on strategy of using case study for not being a source of generalizable knowledge due to usually a small number cases being used.However, this strategy also shown that case studies are useful not only when conducting an explorative study, but also provide valuable insights when conducting explanatory or descriptive research.Three case studies selected in this paper are EthicCrowd.com in Islamic real estate services and waqf philanthropy, Wakaf Selangor Muamalat (WSM) in regulated financial waqf crowdfunding and WorldWaqf in waqf philanthropy.These cases were selected to represent a diverse set of crowdfunding operations that vary in terms of operations, governance and regulations and risk/return for the participants. As this paper seeks to explore the complex relationship inherent in crowdfunding activities it will mostly rely on the gathering of qualitative data. The data is collected through two ways. The first way is through observation which allows the researcher to, in an unobtrusive way, observe the behaviour of the operators and the platforms. This is possible as the crowdfunding activities takes place in an online public setting, which gives the best observations as the subjects are unaware of them being observed and therefore it doesn’t influence their behaviour.Furthermore, as trust is a social construct that is communicated unconsciously, observations can be the best way to collect data on the reaction and behavior of the subjects. Another of source comes from seminars organized by the organizers and a question and answer (Q& A) sessions. These platforms had provided access to data that helped to guide the writing process towards answering the research question. However, as trust and credibility are communicated and presented unconsciously, most observational data from the net is used to analyze the waqf crowdfunding relationship.The second way is through semi structured interviews. Each interview conducted began with explanation of the method and description of the research interest. We had accordingly conducted appropriate protocols for the semi structured. The advantage to this research approach is the ability to collect in situ data, not just reflective data. However, the disadvantage is that bias is introduced through self-report and participant observation.During the analysis stages, we employed a selective coding and analysis. A comparative tabulated matrix based on thematic approach were used to portray the comparative elements through the projects or campaigns, donation collections as well as the flow of operating service models.Findings - The findings have implications on the understanding of agency theory for service managers running philanthropic waqf based entities who are interested in launching and/or managing crowdfunding initiatives, and for distribution theory in terms of extending the donators’ role from just giving away to seeing the impact through profiling reporting. The key findings of this paper are that crowdfunding can provide a viable alternative for waqf entities to attain funding for their projects by cooperating with reliable organizers especially the Islamic fintech companies who act as the trustees and agents.Trustworthiness and credibility are found as essential to signal to the online community who have little protection on the transactions. Only by providing this that the donation for waqf fund could be raised as projected and distributed accordingly.The study suggested that the best way of doing so is to develop a shared social identity where donors feel they become part of a larger group of waqf funding products.